Adherence to Physical Activity Guidelines in the Behavioral Management of Type 2 Diabetes - Czapska, Mirella; Babkiewicz-Jahn, Kamila; Matuszewska, Justyna; Pakaszewski, Wojciech; Wojcik, Alicja (Journal of Education, Health and Sport, 2024)
Introduction and purpose Diabetes comprises a group of metabolic disorders characterized by persistent hyperglycemia. This elevated blood glucose level arises from impaired insulin secretion and/or action. In type 2 diabetes, modifiable risk factors include an unhealthy diet, sedentary lifestyle, and obesity. Given the reversibility of these factors, lifestyle interventions, particularly those promoting physical activity, are deemed beneficial. To evaluate the adherence to type 2 diabetes management guidelines, focusing on the incorporation of physical activity as a critical aspect of behavioral treatment for diabetes. . Materials and methods. Author’s survey covering patients’ knowledge about their disease, needs and expectations regarding education. The questionnaire examines the physical activity of patients newly diagnosed and already treated for type 2 diabetes. Results The most performed exercise among patients was moderate-intensity activities such as walking or Nordic walking. These activities were more frequently intensified compared to others. Patients engaging in these forms of exercise did so more frequently and consistently than those participating in other types of physical activity. Additional activities included running and cycling, predominantly among the younger patient cohort. Patients who derived enjoyment from physical exercise demonstrated a higher likelihood of regular and willing participation. Conclusions. Patients exhibited reluctance to engage in physical exercise and typically did not regard it as a crucial component of their treatment regimen. The exercise they performed was generally of low intensity, and few patients increased their physical activity following their diagnosis. A significant number of respondents lacked understanding of the role of exercise in the management of their condition and its effect on blood glucose levels.